2013
DOI: 10.3892/br.2013.211
|View full text |Cite
|
Sign up to set email alerts
|

High glucose-induced resistance to 5-fluorouracil in pancreatic cancer cells alleviated by 2-deoxy-D-glucose

Abstract: Abnormal glucose metabolism from hyperglycemia or diabetes aggravates the progression of pancreatic cancer. It is unknown whether high glucose has an impact on the antitumor effect of 5-fluorouracil (5-Fu) and whether targeting aberrant glucose metabolism using 2-deoxy-D-glucose (2-DG) may reverse this effect in high-glucose microenvironments. The cell viability of AsPC-1 and Panc-1 was analyzed by MTT assay following 5-Fu treatment at different glucose concentrations. Altered sensitivity to 5-Fu by 2-DG was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Valera et al [64] found that a non-toxic 5 mM 2-DG concentration sensitizes bladder cancer cells to doxorubicin, cisplatin, and gemcitabine, but not mitomycin C or 5 fluorouracil (5-FU). However, in a pancreatic tumor model, 2-DG was able to sensitize cells to 5-FU, indicating a cell-specific effect [73].…”
Section: -Dg and Cytotoxic Chemotherapeuticsmentioning
confidence: 95%
See 2 more Smart Citations
“…Valera et al [64] found that a non-toxic 5 mM 2-DG concentration sensitizes bladder cancer cells to doxorubicin, cisplatin, and gemcitabine, but not mitomycin C or 5 fluorouracil (5-FU). However, in a pancreatic tumor model, 2-DG was able to sensitize cells to 5-FU, indicating a cell-specific effect [73].…”
Section: -Dg and Cytotoxic Chemotherapeuticsmentioning
confidence: 95%
“…Due to its ability to inhibit glycolysis and ATP synthesis, disrupt N-glycosylation of proteins, decrease energy metabolism and NADPH levels, and interfere with cellular thiol metabolism, generating oxidative stress, 2-DG appears to be an efficient cytotoxic agent. Importantly, all of these effects are mostly observed in cancer cells, without significant effect on the viability of normal cells [73]. Moreover, a unique ability to affect cancer cells under hypoxic conditions, which often limits traditional cytotoxic agents, has made 2-DG a promising candidate not only for monotherapy, but also as a component of combination therapy with other commercially available drugs, bioactive compounds, and radiotherapy.…”
Section: Preclinical and Clinical Studies Of 2-dg In Anticancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…5B). LY294002 is a well-characterized inhibitor of PI3K (40), and the effect of combined AFC (100 µg/ml) and LY294002 (10 µM) on the expression of p-Akt/Akt and p-mTOR/mTOR on HCT-116 cells was investigated by western blotting. The results revealed that the combination of AFC and LY294002 treatment was more effective in decreasing of the ratios of p-Akt/Akt (P<0.001) and p-mTOR/mTOR (P<0.05) compared with AFC or LY294002 alone ( Fig.…”
Section: Inhibition Of Autophagy Enhances Afc-induced Apoptosis Inmentioning
confidence: 99%
“…An enhanced antioxidant capacity allows cancer cells to not a universal finding, and mitochondrial respiration impairment is not a fixed feature of cancer cells [41] . Although the glycolytic inhibitors targeting the Warburg effect have been investigated in various cancer types, the glycolytic inhibitors with the exception of 3-BP (a lactate analog) [18,19, , 3-BrOP (a 3-bromopyruvate derivative) [71][72][73][74] , and dichloroacetate (DCA) have demonstrated low efficacy in arresting tumor growth when used alone [99] ; these inhibitors include 2-deoxy-D-glucose (a glucose analog) [70,[100][101][102][103][104][105][106][107][108][109][110][111][112] , lonidamine (a derivative of indazole-3-carboxylic acid) [113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] , methyl jasmonate on HK , 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen-1-one on PFK [162]…”
Section: Initiation Of Metastasismentioning
confidence: 99%